Autointertextuality in the works of A.I. Kuprin (on the material of the stories “Shulamith”, “Garnet bracelet” and the poem “Forever”) (Филологический класс, 2012)
The article investigates the examples of autointertextuality in the prose and lyrics of Russian Silver Age writer A.I. Kuprin. The author of the article considers the intertextual connections of the stories “Shulamith”, “Garnet Bracelet” and the poem “Forever” as interpenetrating structure that ties together disparate pieces of classic’s art. Intertextual elements in the works by A.I. Kuprin reflect the major trends in Russian literature of the Silver Age, and are the interesting object for the analysis of the Old Testament’s artistic representation.